Effect of Polymyxin on the Bacteriophage Receptors of the Cell Walls of Gram-Negative Bacteria - Koike, Masaatsu (1971)
Treatment of gram-negative bacteria with lethal doses of polymyxin B and colistin resulted in the formation of projections of the outer layer of the cell wall. Phages T3, T4, and T7, which use wall lipopolysaccharide as receptors, were specifically prevented from adsorbing to Escherichia coli B cells treated with polymyxin, whereas phages T1, T2, T5, and T6 were not. In the systems of phage P22C-Salmonella typhimurium LT2 and phage C21-S. typhimurium variant SL1069, the phage were prevented from adsorbing to the host cell treated with the antibiotics. Electron microscopic observations show that phage T2 adsorbed irreversibly to the normal smooth surface between the projections on the outer layer caused by the drug treatment. These results indicate that lipopolysaccharide is affected by polymyxin functionally and morphologically, but lipoprotein is not. The purified lipopolysaccharide showed a ribbon-like structure when viewed face on and showed trilamellar structure when viewed edge on. The lipopolysaccharide from E. coli B was irreversibly adsorbed by phages T3, T4, and T7, but not phage T2. Often, phage T4 adsorbed to both sides of the lipopolysaccharide strand at comparable distances. Phage P22C adsorbed through the spikes of the tail-plates to the lipopolysaccharide from S. typhimurium LT2. Lipopolysaccharide which was treated with low doses of the drug (2.5 to 6.25 μg of polymyxin B per ml to 100 μg of lipopolysaccharide per ml) turned into the coiled form and was partially broken down into short segments with coiled form. The loosely coiled lipopolysaccharide retains both its function as the receptor and its trilamellar structure. Treatment with high doses of the drug (12.5 to 25 μg of polymyxin B per ml to 100 μg of lipopolysaccharide per ml) caused the collapse of the trilamellar structure of the strand. These collapsed lipopolysaccharides became flat and fused with each other, making an amorphous mass, and finally they were broken into small collapsed fragments.